2013
DOI: 10.1021/jf400298c
|View full text |Cite
|
Sign up to set email alerts
|

Rosemary (Rosmarinus officinalisL.) Extract Regulates Glucose and Lipid Metabolism by Activating AMPK and PPAR Pathways in HepG2 Cells

Abstract: An epidemic of metabolic disorders such as obesity and diabetes is rising dramatically. Using natural products as potential preventive and therapeutic interventions for these disorders has drawn worldwide attention. Rosemary has been shown to lower blood glucose and cholesterol levels and mitigate weight gain in several in vivo studies. However, the mechanisms are essentially unknown. We investigated the effects of rosemary extract on metabolism and demonstrated that rosemary extract significantly increased gl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
52
0
2

Year Published

2013
2013
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 103 publications
(58 citation statements)
references
References 49 publications
(101 reference statements)
2
52
0
2
Order By: Relevance
“…Statistical significance was set as * p < 0.05, **p < 0.01, or ***p < 0.001, ns: no significance. Tu et al, 2013). Adiponectin (Ad) plays a crucial role in hepatic lipid metabolism, which has been shown to activate the AMPK signaling pathway and mediates lipid metabolism in bovine hepatocytes in vitro by promoting lipid oxidation, suppressing lipid synthesis and reducing hepatic lipid accumulation .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Statistical significance was set as * p < 0.05, **p < 0.01, or ***p < 0.001, ns: no significance. Tu et al, 2013). Adiponectin (Ad) plays a crucial role in hepatic lipid metabolism, which has been shown to activate the AMPK signaling pathway and mediates lipid metabolism in bovine hepatocytes in vitro by promoting lipid oxidation, suppressing lipid synthesis and reducing hepatic lipid accumulation .…”
Section: Discussionmentioning
confidence: 99%
“…LKB1, a crucial regulator of AMPK activation, is implicated in the glucose and lipid metabolism (Imai et al, 2006). Rosemary potentially increases liver glycolysis and fatty acid oxidation by activating AMPK and PPAR (Peroxisome Proliferator-Activated Receptors) pathways (Tu et al, 2013). On the other hand, the pharmaceutical inhibition of AMPK activity by atypical antipsychotic drugs (AAPD) deregulates hepatic lipid metabolism (Oh et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…25 C2C12 myocytes were treated with SE or metformin, resveratrol for 16 h. At that time, the medium was changed to unbuffered serum-free DMEM (Seahorse Bioscience) without glucose for 1 h. The measurement protocol used is as follows 25 : After four baseline measurements, 10 mM glucose and 100 mM 2-deoxyglucose (2-DG) were injected sequentially. For each injection, the ECAR value was monitored at four successive 4-min intervals, with a 2-min inter-measurement mixing.…”
Section: Glycolysis Assaymentioning
confidence: 99%
“…3 Obesity, diabetes, hyperlipidemia, and the consumption of soft drinks are the potential risk factors of NAFLD. 4,5 Pharmaceutical anti-NAFLD drugs have been developed, but these drugs have limited effects, except for pioglitazone and vitamin E. Recently, many studies reported that natural products, such as rosemary extract, 6 were investigated as potential therapeutics for NAFLD. 7 AMP-activated protein kinase (AMPK) has been implicated as a regulator of lipid synthesis by decreasing free fatty acid delivery from hepatic cells 8,9 and mediating lipid metabolism through lipid-metabolism-related transcription factors, such as sterol regulatory element-binding protein-1 (SREBP-1).…”
Section: ■ Introductionmentioning
confidence: 99%